O jogo infantil e a brincadeira numa abordagem sociocultural - Funicelli, Ana Cláudia dos Santos (2008)
This present dissertation is the product of a research about the application of games and jokes in the childlike education. Elements found in all the societies, healthy integral of the worthy assembly that cross generations, carry enjoyment and please, examples of conduct and standards of behavior. The objective of this study is going to verify like the application of the game and of the joke interferes in the trial of education-learning, helping the assimilation of contents and the formation of the knowledge of infants in preschool age. The contextualization of the game as social phenomenon, defended by theoreticians of the Education, does not permit to mere simplistic vision of the game characterized by the leisure and entertainment. It is necessary mature approach, in that sociocultural panoramas detach the relevance of playful in the assimilation of the contents. Falls to teachers to adequate application of these instruments in the classroom. His action is eyeliner of the trial of formation of the knowledge. Is stimulated by compatible games with his age, the infant develops the creativity and interacts with the world to the its around, understanding diverse situations and transforming itself in agent of its own development.